Patterns of HIV, TB, and non-communicable disease multi-morbidity in an informal peri-urban setting in Cape Town, South Africa - Oni, Tolu (Department of Public Health and Family Medicine, 2015)
BACKGROUND: Many low and middle-income countries are experiencing colliding epidemics of chronic infectious (ID) and non-communicable diseases (NCD). As a result, the prevalence of multiple morbidities (MM) is rising. METHODS: We conducted a retrospective study to describe the epidemiology of MM in a primary care clinic in Khayelitsha, an informal township in Cape Town. Adults with at least one of HIV, tuberculosis (TB), diabetes (T2DM), and hypertension (HPT) were identified between Sept 2012-May 2013 on electronic databases. Using unique patient identifiers, drugs prescribed across all facilities in the province were linked to each patient and each drug class assigned a condition. RESULTS: These 4 diseases accounted for 45% of all prescription visits. Among 14364 chronic disease patients, HPT was the most common morbidity (65%). 22.6% of patients had MM, with an increasing prevalence with age, and a high prevalence among younger antiretroviral therapy (ART) patients (26% in 18-35yr and 30% in 36-45 year age groups). HPT and T2DM prevalence was higher a mong younger ART patients with MM compared to those not on ART. Of note, 37% of TB MM patients were also on treatment for H PT and 12% were on treatment for T2DM respectively, and 86% of T2DM patients were on HPT treatment. CONCLUSION: We highlight the co-existence of multiple ID and NCD. This presents both challenges (increasing complexity and the impact on health services, providers and patients), and opportunities for chronic diseases screening in a population linked to care. It also necessitates re-thinking of models of health care delivery and calls for policy interventions that integrate and coordinate management of co-morbid chronic diseases.